Colorimetric and ON–OFF–ON fluorescent chemosensor for the sequential detection of Cu(ii) and cysteine and its application in imaging of living cells. Issue 83 (23rd August 2016) - Singh, Yadvendra; Arun, Shiva; Singh, Brijesh Kumar; Dutta, Pradip Kumar; Ghosh, Tamal
Abstract : An easy-to-prepare colorimetric and ON–OFF–ON fluorescent naphthol derivative1 has been used for sequential detection of Cu 2+ and cysteine. Abstract : An easy-to-prepare colorimetric and ON–OFF–ON fluorescent naphthol derivative1 has been synthesized and characterized for sequential detection of Cu 2+ and cysteine. Chemosensor1 detects Cu 2+ selectively in DMSO/H2 O (3 : 7 v/v) by changing its UV-visible spectrum and color (colorless to yellow), leading to the formation of1 -Cu(ii ) complex. The resultant1 -Cu(ii ) complex recognizes cysteine (Cys) and the solution turns colorless with regeneration of the absorption band of1 . The detection limit of1 for Cu 2+ ion is found to be 0.27 μM, which is much lower than that recommended by WHO for drinking water (30 μM). Cu 2+ ion exhibits quenching of the fluorescence intensity of1, which is restored upon the addition of cysteine. Chemosensor1 is used as an imaging reagent for detection of the cellular uptake of Cu 2+ ion in A549 cell line (human lung carcinoma cell).